Foreign Direct Investors Shun Zimbabwe to Spark a Liquidity Crisis in the Country (2013 a 2014) (Global Journal of Management and Business Research, 2014)
In this Paper the Author looks at how and why the foreign direct investors have shunned Zimbabwe to plunge the country into a liquidity crisis which has since worsened after the disputed 31 July 2013 poll. The period of focus is 2013 to 2014. To wrap up the discourse the Author will proffer a Summary, Conclusion and Recommendations designed for risk treatment to improve the deteriorating liquidity crisis in the country.
Keywords: investors; zimbabwe; liquidity; crisis and global fund